2021
DOI: 10.3390/healthcare9050494
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Selected Bacterial Strains on the Stress Response

Abstract: Introduction: The composition of the microbiome is subject to a variety of factors, such as eating behavior and the history of medical treatment. The interest in the impact of the microbiome on the stress response is mainly explained by the lack of development of new effective treatments for stress-related diseases. This scoping review aims to present the current state of research regarding the impact of bacterial strains in the gut on the stress response in humans in order to not only highlight these impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
(193 reference statements)
0
3
0
Order By: Relevance
“…Probiotics can influence the body’s response to stress and help regulate cortisol levels. By promoting a balanced stress response, probiotics may assist in regulating adrenal hormone production and mitigating the harmful effects of stress-induced oxidative stress ( 188 ).…”
Section: Role Of Nutritional Antioxidants In Alleviating Adrenal Horm...mentioning
confidence: 99%
“…Probiotics can influence the body’s response to stress and help regulate cortisol levels. By promoting a balanced stress response, probiotics may assist in regulating adrenal hormone production and mitigating the harmful effects of stress-induced oxidative stress ( 188 ).…”
Section: Role Of Nutritional Antioxidants In Alleviating Adrenal Horm...mentioning
confidence: 99%
“…Another important aspect is the differences in microbiome structures in organisms subjected to stress, whether because of effects of system intensity, environmental contamination, temperature, and/or nutritional deficiencies. Studies have shown that stress, particularly chronic stress, and microbial manipulation (probiotics or prebiotics) influence the microbiome structure of the fish gut (Anker‐Ladefoged et al, 2021; Rimoldi et al, 2020; Serradell et al, 2020). However, there is still insufficient information on the influence of nutritional, environmental, or genetic factors on the microbiome on fish growth and health to assess the economic benefits of adding probiotics in the feed or water.…”
Section: Requirementsmentioning
confidence: 99%
“…Probiotics (or named direct-fed microbials) have been defined as: “live microorganisms which when administered in adequate amount confer a health benefit on the host” [ 21 , 22 ]. Numerous probiotics such as Lactobacillus plantarum and Bifidobacterium lactis have been used as dietary supplements or functional foods with therapeutic potential to target gut microbiota for the prevention or potential therapeutic treatment of mental diseases including social stress-induced psychiatric disorders such as depression, anxiety, and schizophrenia [ 15 , 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Similar function of the probiotics via modification of the gut microbiota may present in poultry.…”
Section: Introductionmentioning
confidence: 99%